Marketing Strategy of SD Muhammadiyah 1 Sedati: Strategi Pemasaran Sd Muhammadiyah 1 Sedati - Mochammad Kohar (Academia Open, 2021)
An interesting phenomenon occurs in the implementation of education, especially when new students are accepted. People seem to have understood which schools are appropriate to send their sons/daughter to, for them the criteria for schools that have a good image are schools that succeed in satisfying educational service users (users). The research was conducted at SD Muhammadiyah 1 Sedati which in fact includes a newly established school that is able to compete with other schools in the surrounding environment. The focus of this research is; 1). What is the marketing strategy at SD Muhammadiyah 1 Sedati, 2). What are the strengths of SD Muhammadiyah 1 Sedati as a new educational institution to market educational institutions. This research includes qualitative research. The results of this study are: (1). Education services at SD Muhammadiyah 1 Sedati prioritize efforts to fulfill customer expectations and satisfaction, (2). Marketing Strategy in improving the image of the school. However, an effective strategy at SD Muhammadiyah 1 Sedati is to build an image of service satisfaction through word of mouth and by using the power of the Muhammadiyah Sedati Branch Manager (3). The impact of the marketing strategy and its implications for imaging at SD Muhammadiyah 1 Sedati are as follows; a). High customer loyalty of education service users (public understanding). b). Public confidence is getting stronger (public confidence), c). The existence of community support (public support), d). Establishing effective cooperation between schools and parents (public corporation)